حسن شمران محمد تقيم بعض المواصفان النوعيه للخل المتداول في اسواق مدينة الديوانية - شمرانحسن (University of Thi-Qar Journal of Science, 2019)
In this study we measured some qualifications which indicate the scope of contamination or idenfication of some kinds of vinegar existing in Diwania markets to qualitative Iraqi and international standards . Acidic factor (pH) has been checked between 2.5 - 3.29 for various samples , Total acidity has been checked by guidance of acetic acid ranging between 3.5 - 15.6 % for various samples of vinegar . The total ash is ranging between 0.06 – 1.11% . The total ratio of solid materials is ranging between0.13 - 1.50 % . The results indicated that all these variables ranged within admissible limits for natural vinegar except the ratio of acetic acid in some samples examined which were higher than accepted limits (4 - 8 %). Some samples of vinegar under study have been examined to know the extent of their contamination due to some materials like Lead , Copper , iron and zinc . The results indicated that these samples contained one part from million parts as follows :- (0.01 – 0.31 , 0.25 – 0.51 , 0.16 – 0.41 , 0.26 – 0.51) , These ratios are with admissible limits according to Iraqi and international standards .